Theoretical Analysis of Concentration Polarization Effect on VOC Removal by Pervaporation - S. X. Liu; L. M. Vane; M. Peng (Journal of Hazardous Substance Research, 2003)
Pervaporation is an innovative membrane-based separation technology for volatile organic compound (VOC) removal from contaminated groundwater. Concentration polarization is a process phenomenon occurring in pervaporation and several other membrane-based separation technologies. Concentration polarization, defined as concentration gradient of permeating solute between the bulk and the region near the membrane surface, becomes a limiting factor in pervaporation separations using high-performance membrane materials in VOC removal operations. Thus, the ability to predict the impact of concentration polarization upon process performance is highly desirable in process design and optimization. A mathematical model was developed to illustrate the interplay between concentration polarization and process performance in pervaporation operation of VOC removal in a membrane channel with rectangular cross section. By incorporating pervaporative mass transfer, laminar hydrodynamics, and boundary-layer theory, the model was built to allow theoretical analysis of the sensitivity of flow velocity, feed concentration, and concentration polarization index (CPI) upon the transmembrane flux and longitudinal mass flow.
Keywords: pervaporation; concentration polarization; VOC removal; boundary-layer mass transfer